Korean Brand Ambassador and Trust: A Pathway to Repurchase Intention in Scarlett Whitening Skincare - Rimadias, Santi; Pasha, Faradilla (STIE Indonesia Banking School, 2025)
This study explores the role of Korean brand ambassadors and trusts in purchase decisions and the subsequent effect on repurchase intention for Scarlett Whitening skincare products. Using a quantitative research approach, data was collected from 110 respondents aged 17 years and older who had previously purchased Scarlett Whitening skincare products. The study used Partial Least Squares Structural Equation Modeling (PLS-SEM) and was analyzed using SmartPLS 3.0 software, which combines the evaluation of Outer and Inner models to ensure robust data processing. The findings revealed that the presence of Korean Brand Ambassadors and Trust significantly influenced purchase decisions, which in turn played a crucial role in shaping repurchase intent. These insights highlight the strategic importance of leveraging Korean Brand Ambassadors and strengthening consumer trust to increase long-term brand loyalty. This study provides valuable implications for the management of the Scarlett Whitening brand, by emphasizing the need to identify and optimize the key factors driving consumer retention and repeat purchases in the competitive skincare market.